A high reliability and low latency routing algorithm in cognitive wireless mesh networks. (2017) - Kuang, Zhufang; Chen, Zhigang
A channel utility value computing (CUVC) algorithm is proposed. The channel utility value contains channel usage probability and channel stability. A high reliability and low latency wireless link weight computing algorithm (RL2W) is proposed. On this basis, a high reliability and low latency routing and spectrum allocation algorithm based on dynamic programming in cognitive wireless mesh networks (HRL2A) is proposed. High reliability and low latency route is the objective of HRL2A. Firstly, HRL2A computes the channel utility value using CUVC for constructing the high reliability route. Secondly, HRL2A uses the algorithm RL2W computing wireless link weight. Thirdly, the route of high reliability and low latency is constructed based on dynamic programming, and the wireless link channel is allocated. Simulation results show that HRL2A algorithm can achieve expectation goal. The construction route not only has higher reliability, but also has lower latency. The throughput has been increased.